Chemical properties and composition of PM emitted from a diesel engine fueled with ternary fuel (diesel-biodiesel-ethanol) in blended and fumigation modes. (1st September 2019) - Ghadikolaei, Meisam Ahmadi; Yung, Ka-Fu; Cheung, Chun Shun; Lau, Pak-Chung
Highlights: Diesel PM has total carbon (85.8%), ions (1.9%) and metals and elements (0.7%). D80B5E15 fuel in blended or fumigation mode changes the PM chemical properties. Blended mode can has positive effect on diesel particulate filter (DPF) efficiency. Fumigation mode has lesser effect than blended mode on DPF efficiency. Fumigation + blended mode has impacts in between the fumigation and blended modes. Abstract: This experimental study aims to investigate the effects of different fueling modes, including diesel, blended, fumigation and fumigation + blended (F + B) modes, on the chemical properties and composition of particulate matter (PM) of a diesel engine fueled with diesel-biodiesel-ethanol fuel (D80B5E15, volume %) under four operating conditions. It is found that the use of DBE has different effects on the chemical properties and composition of PM in the blended mode or the fumigation mode. The blended mode has higher organic carbon (OC)/total carbon (TC) ratio, but lower TC, OC, elemental carbon (EC), EC/TC ratio, water-soluble organic carbon, inorganic ions, metals and elements compared to those of the fumigation mode. For the PM composition, the diesel mode has the highest ratios of TC (85.8%), EC (47.6%) and inorganic ions (1.9%) and the lowest ratios of OC (38.2%), metals and elements (0.7%) and unknown species (11.6%). In contrast, the lowest ratios of TC (80.4%), EC (28.0%) and inorganic ions (1.6%) and the highest ratios of OC (52.4%) and unknown species (16.7%) are found for the blended mode. The highest metals and elements ratio (1.4%) is found in the fumigation mode. The F + B mode has the impacts between those of the fumigation and blended modes.